Colonization and Spore Richness of Arbuscular Mycorrhizal Fungi in Araucaria Nursery Seedlings in Curitiba, Brazil - Carlos Vilcatoma-Medina; Glaciela Kaschuk; Flávio Zanette (International Journal of Agronomy)
Araucaria or Paraná pine [Araucaria angustifolia (Bertol.) Kuntze, 1898] is an endangered timber tree species of Atlantic Forest that naturally forms symbiosis with arbuscular mycorrhizal fungi (AMF). The objective of this experiment was to evaluate AMF colonization and spore AMF richness in araucaria seedlings produced in nursery at the metropolitan region of Curitiba, Brazil, with the interest of identifying a taxonomical AMF group. For that, soil and fine roots of 6-month-, 1-year-, 2-year-, 3-year-, and 5-year-old araucaria seedlings were sampled and evaluated. Evaluations indicated that araucaria seedlings were well colonized by AMF (with rates varying from almost 50 to over 85%) and produced an abundant number of mycorrhizal spores (from 344 to 676 spores per seedling). Samples contained spores of the species Acaulospora scrobiculata, Dentiscutata heterogama, and Glomus spinuliferum and unidentified species of genera Gigaspora and Glomus. The Glomus genus was the most abundant kind of AMF spores found under nursery conditions. Therefore, the experiment evidenced that Glomus is a promising genus candidate for being used as AMF inoculant in production of araucaria seedlings.